(untitled) (East West Medical College Journal, 2026)
Background: Accessory foramina of the middle cranial fossa are clinically significant anatomical variants that may alter neurosurgical approaches and radiological interpretations. Among these, the caroticoclinoid foramen (CCF) and foramen Vesalius (FV) are of considerable importance because of their close relationship with the cavernous sinus, internal carotid artery, trigeminal ganglion, and emissary venous channels.The caroticoclinoid foramen occurs due to the ossification of the caroticoclinoid ligament or dural fold stretching between the anterior and middle clinoid processes. The small foramen of Vesalius occurs in approximately 20% of skulls; it is consistently symmetrical and lies anteromedial to the foramen ovale, lateral to the foramen rotundum, and adjacent to the vidian canal. This foramen transmits an emissary vein, through which the cavernous sinus and pterygoid plexus communicate. The presence of the emissary vein in this foramen is significant for transmitting sepsis from extracranial veins to intracranial venous sinuses, as well as in neurosurgical techniques such as radiofrequency rhizotomy. Objective: The caroticoclinoid foramen may complicate clinoidectomy procedures. Therefore, detailed anatomical knowledge of the region is necessary to obtain satisfactory results from these surgeries. An anatomical study of the foramen of Vesalius contributes not only to the anatomical knowledge of this structure, but also to clinical situations involving this foramen. Materials & Methods: A cross-sectional, analytical study was conducted in the Department of Anatomy of Dhaka Medical College, Dhaka, from January 2011 to December 2011. The study materials consisted of 117 (one hundred and seventeen) dry ossified human middle cranial fossa. Results: The caroticoclinoid foramen was present in 4% of cases on both sides, respectively. Foramen Vesalius was present in 27% on the right side and 30% on the left side. Conclusion: Accessory foramina of the middle cranial fossa, particularly the foramen Vesalius, are relatively common. Awareness of these anatomical variations is essential for anatomists, neurosurgeons, ophthalmologists, and radiologists to ensure accurate diagnosis and to reduce complications during skull base surgery. EWMCJ Vol. 14, No. 2, July 2026: 157-161